THE CONTROVERSY OF APPLYING THE DEATH SENTENCE FOR CRIMINAL ACTS RELATED TO DRUGS - Hasan Asy’ari, Syamsul Hidayat & (Jurnal IUS, 2013)
In anticipation of the threat and the dangers of drug abuse and illicit trafficking, Indonesia as a whole has had the law on ratification of the Convention , including the United Nations on combating illicit trafficking in narcotic drugs and psychotropic substances in 1988. Policy is required drug crimes (penal policy). Applicable policies regarding how to commit criminal law legislation in force at the moment and formulated policies that lead to renewal (penal law reform) who formulated the laws of criminal law . The global trend will be a moratorium on the death penalty, the idea of humanism or universal human values sometimes correlated inversely with the application giving rise to the defense of the human rights perspective. Dynamics in the world of criminal law shifted from theory to theory retaliation treatment clinic . Policy on the death penalty in law on drugs illustrates the manifestation of the idea of balance or mono-dualistic and offer alternative policies forward in line with the function and purpose of the law-making in the context of national law in Indonesia .Keywords : Capital Punishment, Narcotics, Moratorium